Patient reported outcomes 6 to 12 months after interpersonal violence: A multicenter cohort study. Issue 2 (August 2021) - Castillo-Angeles, Manuel; Herrera-Escobar, Juan P.; Toppo, Alexander; Sanchez, Sabrina E.; Kaafarani, Haytham M.; Salim, Ali; Haider, Adil H.; Nehra, Deepika
Abstract : PURPOSE: Violence continues to be a significant public health burden, but little is known about the long-term outcomes of these patients. Our goal was to determine the impact of violence-related trauma on long-term functional and psychosocial outcomes. METHODS: We identified trauma patients with moderate to severe injuries (Injury Severity Score, ≥9) treated at one of three level 1 trauma centers. These patients were asked to complete a survey over the phone between 6 and 12 months after injury evaluating both functional and psychosocial outcomes (12-item Short Form Survey, Trauma Quality of Life, posttraumatic stress disorder [PTSD] screen, chronic pain, return to work). Patients were classified as having suffered a violent injury if the mechanism of injury was a stab, gunshot, or assault. Self-inflicted wounds were excluded. Adjusted logistic regression models were built to determine the association between a violent mechanism of injury and long-term outcomes. RESULTS: A total of 1, 050 moderate to severely injured patients were successfully followed, of whom 176 (16.8%) were victims of violence. For the victims of violence, mean age was 34.4 years (SD, 12.5 years), 85% were male, and 57.5% were Black; 30.7% reported newly needing help with at least one activity of daily living after the violence-related event. Fifty-nine (49.2%) of 120 patients who were working before their injury had not yet returned to work; 47.1% screened positive for PTSD, and 52.3% reported chronic pain. On multivariate analysis, a violent mechanism was significantly associated with PTSD (odds ratio, 2.57; 95% confidence interval, 1.59–4.17; p < 0.001) but not associated with chronic pain, return to work, or functional outcomes. CONCLUSION: The physical and mental health burden after violence-related trauma is not insignificant. Further work is needed to identify intervention strategies and social support systems that may be beneficial to reduce this burden. LEVEL OF EVIDENCE: Prognostic and epidemiological, level III.